FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMOTIVASI PETANI DALAM USAHATANI LADA (Piper nigrum L.) (Studi Kasus di Kawasan Perbatasan Desa Bambangan Kecamatan Sebatik Barat Kabupaten Nunukan) (Socio-economic Factors Motivating Farmers in Pepper Farming (Piper nigrum L.) (Case Study in Border Area of Bambangan Village West Sebatik Subdistrict Nunukan District) - ERIMUS DAMASUS; MIDIANSYAH EFFENDI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2019)
Pepper is one of the leading commodity in Indonesia especially in North Kalimantan Province. Pepper becomes world trade commodity so that motivates farmers to do pepper farming. Motivation is influenced by several social and economic factors namely education, profession, work opportunity,  market, selling price, and income. This study aimed to determine the socio-economic factors motivating farmers to do pepper farming in Bambangan Village, West Sebatik Subdistrict, Nunukan District. The study was conducted from June until August 2018 in Bambangan Village, West Sebatik Subdistrict, Nunukan District. The research method was done by simple random sampling with 33 respondents. Data analysis used Likert scale with three indicators of socio-economic that motivate farmers in the application of pepper farming. The result showed that social factors determine with a score of 1,022 or equal to 30.96 motivate farmers in the application of pepper farming and economic factors determine with a score 717 or equal to 21.72. Socio factors is dominant of work opportunity with a score of 96.96%. Socio-economic factors determine the motivation of farmers in the application of pepper farming in Bambangan Village.